An Observation on Set-valued Contraction Mappings in Modular Metric Spaces: Parin Chaipunya, Poom Kumam - Team, Support (Thai Journal of Mathematics, 2015)
We present in this paper the existence criteria of a fixed point of a set-valued contraction in modular metric space. Our results also fix the error in the preced- ing paper [3, P. Chaipunya, C. Mongkolkeha, W. Sintunavarat, and P. Kumam, Fixed-point theorems for multivalued mappings in modular metric spaces, Ab- stract and Applied Analysis, 2012:14, 2012.], with some extra hypotheses.